THE PROBLEM OF DETERMINING THE COMPETENCES OF TEACHER TECHNOLOGIES TO MAKE EFFECTIVE PEDAGOGICAL ACTIVITY (Pedagogy of Higher and Secondary Education, 2009)
In article the definition problem competence teachers of technologies with which help probably to provide not only the international recognition of diplomas, and a recognition of their professional suitability has been opened.
Keywords: competence; key competence; teacher of technologies; knowledge; abilities